Colonial legacies in a fragile republic a history of Philippine land law and state formation with emphasis on the early U.S. Regime (1898-1913) - Lynch, Owen J. (U.P. Law centennial textbook writing project, 2011)
This book is a revised and slightly updated version of unpublished Doctor of Laws dissertation of Owen J. Lynch which was finished in 1991.The dissertation was awarded Yale University's Ambrose Gherini Prize for the best paper on an international law topic in 1992.And now this dissertation is being published for the first time in its entirety in 2011 as part of the commemorations celebrating the centennial anniversary of the University of the Philippines College of Law.